Robert Frost’s Philosophical Views on Nature In His Selected Poems (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2018)
Abstrak Mempelajari pandangan semiotik dan filosofi akan mengarah pada diskusi topik menarik. Topik yang tidak pernah berakhir tentang pandangan filosofis terutama karena topik ini adalah tentang perilaku manusia. Hal ini mirip dengan apa yang dibahas dalam penelitian ini yang berjudul Pandangan Filosofis Robert Frost tentang Alam dalam Puisi yang Dipilihnya. Penelitian ini akan berfokus pada masalah yang diajukan ke dua pertanyaan utama (1) Apa makna di balik simbol puisi Robert Frost? Dan (2) Bagaimana pandangan Robert Frost tentang alam? Metode yang digunakan dan pendekatannya diklasifikasikan ke semiotika dimana tanda dan simbol dibicarakan dalam puisi terpilih Frost untuk menjawab pertanyaan nomor satu dan ekopsikologi untuk menjawab pertanyaan nomor dua. Yang terakhir, hasilnya menggambarkan bahwa simbol alam yang ada dalam puisi terpilih Frost; “The Road Not Taken”, “Tree at My Window”, ”Fire and Ice”, “Nothing Gold Can Stay”, & “Birches”dan apa yang mempengaruhi oleh puisi Robert Frost dengan pandangan filosofisnya. Kata kunci: Puisi, Semiotika, Ekopsikologi dan Pandangan Filosofis. Abstract Learning about semiotic and philosophical views will lead into interesting discussion topics. Philosophical view is a never ending topic to be mainly discussed because the topic is about human behaviour. It is similar to what is discussed in this study, entitled Robert Frost’s Philosophical Views on Nature in His Selected Poems. This study will focus on the problems which are delivered to the two main questions: (1)What are the meanings behind the symbols in Robert Frost’s selected poems; and (2)How are Robert Frost’s views about nature?. The applied method and approach are classified to semiotics where the sign and symbol are being talked about in Frost’s selected poems to answer the first question, whereas ecopsychology is applied to answer the second question. The last, the result describes about the nature symbols which exist in the Frost’s selected poems; “The Road Not Taken”, “Tree at My Window”, ”Fire and Ice”, “Nothing Gold Can Stay”, & “Birches” and the influence of the nature poem of Robert Forst with his philosophical view. Key words: Poems, Semiotics, Ecopsychology and Philosophical view.